A moderated mediation model of green space exposure, mindfulness, physical activity level, and perceived stress - Lin, Yuanzheng; Ma, Xiujie; Zhao, Bin; La, Changxu; Zhang, Peng; Luo, Qingyuan (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to explore how urban green space exposure influences individuals’ perceived stress levels, focusing on the mediating role of mindfulness and the moderating role of physical activity.MethodsA cross-sectional survey was conducted in Chengdu, China, with 318 adult residents. Validated scales were used to assess green space exposure, mindfulness, physical activity, and perceived stress. Structural equation modeling and the PROCESS macro (Model 4 and Model 8) were used to test the mediation and moderated mediation effects.ResultsGreen space exposure was found to significantly reduce perceived stress both directly and indirectly via enhanced mindfulness. Mindfulness partially mediated the relationship between green space exposure and stress perception. Moreover, physical activity moderated both the green space–mindfulness and green space–stress pathways. Specifically, individuals with higher levels of physical activity experienced greater mindfulness gains from green exposure, while those with lower activity levels experienced stronger stress-relief benefits.ConclusionThis study highlights the dual cognitive and behavioral pathways through which green environments promote mental well-being. The findings provide theoretical insights for designing targeted urban health interventions that integrate green infrastructure with physical activity promotion.